PENGARUH PEMBERIAN TIMBAL (Pb) TERHADAP PERTUMBUHAN DUA VARIETAS LADA (Piper nigrum L) - Santi, Ratna; Pratama, Deni; TV, Nababan (Enviagro: Jurnal Pertanian dan Lingkungan, 2023)
The pepper (Piper nigrum L.) a plantation crop that widely cultivated farmers in Indonesia, especially in Bangka Belitung Islands. One of the challenges of pepper cultivation in Bangka Belitung is the reduction in land conversion caused by tin mining. Tin mining causes high levels heavy metal content. The heavy metal lead (Pb) is element that can influence its growth. Pb are will become an inhibitor of enzyme formation which inhibits plant metabolism and effect growh of pepper. The aim of this research to determine the effect of giving Pb to both varieties and determine which varieties are adaptive in planting media containing Pb. This research was carried out April to July, at Bangka Belitung University. The method used was experiment and the design used was a randomized (RAKF). Treatment consists 2 factors. The first factor is Petaling 1 cultivar and the Nyelungkup cultivar. The second factor, Pb concentration which consists of Pb concentration of 0 ppm, 100 ppm and 200 ppm. Data analysis used the F test (ANOVA) followed the Duncan’s Multiple Range Test (DMRT). The research results showed each cultivar did not have a real influence on the observed parameters. Aplication Pb concentrations 100 and 200 Ppm had effect on plant height, number of leaves, increasing number of shoots, leaf area and root length and root fresh weight. Nyelungkup cultivar is a cultivar that is better able to adapt to growing media contaminated with the heavy metal Pb better than Petaling 1.